Deployment of the Ophthalmic and Facial Angiosomes in the Upper Nose Overlaying the Nasal Bones. (9th January 2021) - Cai, Bing; Yuan, Rong; Zhu, Guo-Zhang; Zhan, Wen-Feng; Luo, Cheng-En; Kong, Xiang-Xue; Luo, Sheng-Kang
Abstract: Background: Nasal filler placement is associated with a high risk of blindness. The arterial supply to the upper nose overlaying the nasal bones is poorly understood. Objectives: The aim of this study was to visualize and analyze the deployment of the ophthalmic and facial angiosomes in the upper nose to help prevent blindness following nasal filler injections. Methods: The arterial systems of 62 cadaveric heads were filled with lead oxide contrast agent, and computed tomography (CT) images were acquired and reconstructed in 3 dimensions. Results: Twenty-six of the cadaveric noses examined demonstrated clear CT images of the facial and ophthalmic angiosomes in the upper nose. The Type 1 upper nose (15.4%) is supplied by 2 independent ophthalmic angiosomes that communicate indirectly through a choke anastomosis. The Type 2 upper nose (38.5%) is supplied by 2 ophthalmic angiosomes with a true anastomosis between them. The Type 3 upper nose (46.1%) is supplied by both ophthalmic and facial angiosomes with true anastomoses across the dorsal midline. These true anastomoses are mediated by the radix arcade in 46% of the noses and involve the dorsal nasal artery in 65% of the cases. The anastomoses all cross the upper dorsal midline and are directly linked to the ophthalmic angiosome. Conclusions: The deployment and anastomosis of the facial and ophthalmic angiosomes in the upper nose fall into 3 major patterns. About 85% of the noses have true anastomotic arteries that cross the upper dorsal midline and are directly linked to the ophthalmic circulation. Dorsum filler injection poses a significant risk of blindness.